INDICATORS OF THE RELEVANCE OF THE PRACTICE OF BALLROOM DANCE ON ELDERS´ LIFE STYLE A PILOT STUDY (Fiep Bulletin - online, 2013)
This study deals with the practice of hall dance by the elderly participating in the University Program with the Best Age, promoted by Unipac Vale do Aço, in the town of Ipatinga MG. As research subject, dance is considered a kind of language made up of other artistic languages (music, theatre, literature, fine arts) which, depending on the show presented, or the subject put on, presents a specific language. The dance may be understood as art because it creates expressive forms of human feelings, thus being a means of communication. The investigation had as aim to raise indicators of dance value, as a way of impacting the lifestyle of the elderly participating in the program. We can state that hall dance allows the students to progress, as it broadens their knowledge, sensibility and their relation to the world. As we discover the mystery of dance, we find back pleasure and satisfaction. Dance can be included on the list of leisure activities, as well as on that of activities that promote full “satisfaction”, described in Csikszentmihalyi's flow theory (1992). Besides promoting satisfaction, hall dance can be considered a leisure activity that favors socialization, a factor that is fundamental in an individual's formation.
Keywords: ballroom dance; elderly; lifestyle